Pengaruh Pembelajaran Problem Based Learning Berbasis ChatGPT Terhadap Hasil Belajar Melalui Minat Belajar Di SMKS Budi Agung Medan T.A 2025/2026 - Nurul Hasanah Herzegovani; Dodi Pramana (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The rapid advancement of digital technology and the integration of artificial intelligence in education demand innovative learning models that can enhance student’s motivation and academic performance. Preliminary observations at SMKS Budi Agung Medan revealed low achievement of the Minimum Mastery Criteria (KKM) in the subject Office Activity Fundamentals, accompanied by limited learning interest caused by monotonous teaching methods and an unconducive learning enviroment. This study aims to analyze the effect of ChatGPT-based Problem Based Learning (PBL) on learning outcomes, examine the mediating role of learning interest, and identify the interaction between PBL-ChatGPT and learning interest in influencing student achievement. A quantitative approach with a pre-experimental one-group pretest-posttest design was applied to 29 students of class X MPLB 1. Learning outcomes tests and learning-interest questionnaires were administered, with data analyzed using the Wilcoxon test, N-Gain, and Bootstrapping mediation analysis in SmartPLS. The findings indicate a significant improvement in learning outcomes after implementing PBL-ChatGPT, supported by an Asymp. Sig Value of 0,001 < 0,05 and a moderate N-Gain score. Learning interest was confirmed as a significant mediating variable linking PBL-ChatGPT to learning outcomes. Furthermore, all structural path in the SEM-PLS model were significant, demonstrating a positive interaction between PBL-ChatGPT and learning interest in enhancing student performance. Thus, ChatGPT based PBL is effective as an innovative instructional model for teaching customer service competencies in vocational school.